Untranslatability : interdisciplinary perspectives - Large, Duncan, 1965-; Akashi, Motoko; Józwikowska, Wanda; Rose, Emily (Routledge advances in translation studies, 2019)
This volume is the first of its kind to explore the notion of untranslatability from a wide variety of interdisciplinary perspectives and its implications within the broader context of translation studies. Featuring contributions from both leading authorities and emerging scholars in the field, the book looks to go beyond traditional comparisons of target texts and their sources to more rigorously investigate the myriad ways in which the term untranslatability is both conceptualized and applied. The first half of the volume focuses on untranslatability as a theoretical or philosophical construct, both to ground and extend the term's conceptual remit, while the second half is composed of case studies in which the term is applied and contextualized in a diverse set of literary text types and genres, including poetry, philosophical works, song lyrics, memoir, and scripture. A final chapter examines untranslatability in the real world and the challenges it brings in practical contexts. Extending the conversation in this burgeoning contemporary debate, this volume is key reading for graduate students and researchers in translation studies, comparative literature, gender studies, and philosophy of language.